Clinico-histopathological study of tattoo reactions in tertiary care center - Bhindora, Pooja K.; Patel, Bharti K.; Bhuptani, Neela V.; Surani, Ashma S. (International Journal of Research in Dermatology, 2022)
Background: Tattooing is nowadays very common practice especially among young people and we are witnessing a gradual increase of numerous potential reactions to tattoos. Purpose of this study was to identify the various tattoo reactions and to correlate it with histopathological examination and early interventions to decrease further morbidity. Methods: From December 2017 to September 2019, patients reporting with reactions due to tattooing were included in the present study after obtaining informed consent. A detailed history regarding the onset, duration and colour used for tattooing were collected and noted. Cutaneous examination and biopsy were done in all cases to know the type of reaction. Results: The analysis included 50 patients who had tattoo reactions. The most common age group affected was 16-30 years, with slight male predominance. Most of the cases (64%) with tattoo reaction presented to us within 1 to 4 months of disease presentation. Clinically, most cases had granulomatous reaction 23 (46%). On histopathology, granulomatous reaction was the most common type observed. Red colour dye was the most common colour associated with reaction seen. Clinico-histopathological correlation of various types of tattoo reaction revealed consistency with diagnosis in 17 (34%) patients, clinically as well as on histopathological examination. Conclusions: Lack of strict regulations by government and increased fashion trends increase complications associated with tattoos. Red inks are the most frequently associated with tattoo reactions. Granulomatous type reactions are a frequently reported pattern of inflammation seen in tattoo.